Unlocking access to climate finance for Pacific Island countries - Fouad, Manal,Novta, Natalija,Preston, Gemma,Schneider, Todd T.,Weerathunga, Sureni (International Monetary Fund, Publication Services, 2021)
This departmental paper provides an in-depth overview of access to climate finance for Pacific Island Countries, evaluating successes and challenges faced by countries and proposes a way forward to unlock access to climate funds
10.5089/9781513594224.087
Keywords: Graue Literatur; Pacific Islands; Fiji; Tonga; Tuvalu; Papua New Guinea; Palau; Kiribati; Nauru; Micronesia; Marshall Islands; Samoa; Solomon Islands; Vanuatu; public financial management; small states; island economies; Climate Change; Pacific Islands; Climate Finance and Public Financial Management; GCF Requirement; Climate change; climate finance; Climate; Global Warming; Natural Disasters and Their Management; Public Finance; Natural Disasters; Environmental Economics: General; National Government Expenditures and Related Policies: General; Political economy; International institutions; Environmental economics; Environmental Economics; Public finance & taxation; Environment; Environmental Policy; Public financial management (PFM); Environmental policy; Climatic changes; Finance; Public; Environmental sciences; Natural disasters